The Relationship Between Parental Involvement and Children’s Moral Development PAUD Asmaul Husna Padang City - Fadilla, Daswif Fanny; Ismaniar, Ismaniar (Universitas Negeri Padang, 2023)
This research is motivated by the low moral development of children, this is thought to be caused by parents are less involved in their child’s development. This study aims to (1) describe parental involvement (2) describe moral development of children (3) describe the relationship between parental involvement and the moral development of children in PAUD Asmaul Husna Kota Padang City. This study uses a quantitative approach with a correlational type. The population of this study were parents whose children attended PAUD Asmaul Husna Padang City, totaling 21 people. The sampling technique using cluster random sampling was taken 75% of the population, namely 16 people. Dta collection techniques and data collection tools in the form a list of statements. Data analysis techniques use percentage and rank orders. The result of this study indicate that (1) parental involvement in children in PAUD Asmaul Husna Padang City is categorized as low. (2) Moral development of children in PAUD Asmaul Husna Padang City is categorized as low. (3) The result of data processing show that there is a significant relationship between parental involvement and children’s moral development in PAUD Asmaul Husna Padang City, this is proven and it is found that the results of rcount are greater than rtabel.Keywords: parental involvement, moral development children